PERUBAHAN PARADIGMA BIMBINGAN DAN KONSELING - Muhammad Nur Wangid (Paradigma, 2010)
Guidance and counselling in Indonesia was a relatively young profession. As a new comer profession it has many missled and misconducted, one of them was misunderstanding about guidance and counselling rofession as a static profession. The consequence was the survices of guidance and counseling uncontextual, unfullfil the needs and hopes of society. The aim of this article enlighted the canging of guidance and counselling paradigm from the past, present, and future. On the past school counselling services driven counselling, consultation, and coordination. Now, guidance and counselling should be proactively survices that was leadership, advocacy, teaming and collaboration, assessment and use of data, and technology. On the future intentional and purposefull school counselling program was aligned and integrated with the educational interprise. Accountability, cultural mediation and systemic chane agent was additionally for the all programs that had mentionedKeywords: change; guidance and counselling paradigm